Removal of Ni (II) and Pb (II) ions from aqueous solution using Amberlyst-15 ion exchange resin as an adsorbent - Alamin, Nayma Mohamed Asalmi (2017)
Heavy metals are among the most inorganic hazardous pollutants. Therefore, the removal of metal ions in man-made and natural water sources is essential in order to protect the various ecosystems. Adsorption is by far the most versatile technique for removal of metal ions especially when adsorbent regeneration and reuse could improve cost effectiveness. The high cost and difficulty of separating of activated carbon restrict its application in wastewater treatment. Organic ion exchange resins are found more suitable for the removal of toxic elements due to their faster kinetics, ease of regeneration and high exchange capacity. Thus the present study was aimed to evaluate the potential use of Amb-15 ion exchange resin as a an adsorbent for Ni(II) and Pb(II) metal ions. To achieve this aim, the adsorption experiments were performed to investigate the efficiency of Ni(II) and Pb(II) removal in wide variety of experimental parameters .The adsorption of metal ions onto the adsorbent was found to be highly dependent on the adsorbent dose, the initial concentration of metal ions and contact time. Solution pH showed an uneven positive effect on the metal ions due to the different mechanism dominate the adsorption interactions (ion exchange and chemisorption). Thermodynamics, kinetics and adsorption equilibrium parameters studies suggest, the importance of chemical reaction between Am-15 and the metal ions. The maximum adsorption efficiencies and capacities obtained from the single batch system were 93.3 and 99.9 % and 112.5 and 384.6 mg g-1 for Ni(II) and Pb(II) respectively. Which sufficiently good compared to several ion exchange resin or synthesized adsorbents derived from natural materials. In conclusion, the bath adsorption procedure was applied on Sungai Balok Kuantan Pahang river water sample and up to 80% and 92% removal were obtained for Ni(II) and, Pb(II)respectively. Overall, ion exchanger Am-15 commercially available can be effectively used as an adsorbent for heavy metal removal from the synthetic and natural water sample.